Apigenin attenuates the atherosclerotic lesions through enhancing selective autophagy/lipophagy and promoting RCT process - Zixuan Hu; Yuting Li; Nan Yao; Haining Gan; Qiaohuang Zeng; Xuejun Huang; Dane Huang; Dake Cai; Yuxing Chen (Pharmaceutical Biology)
Context Apigenin, a naturally flavonoid, is reported to have protective effects in chronic and metabolic diseases. But the therapeutic or ameliorative effects of apigenin on atherosclerosis are not known.Objective Our study aimed to elucidate the underlying mechanism of apigenin on preventing atherosclerosis by enhancing selective autophagy/lipophagy and promoting RCT process.Materials and methods ApoE−/− mice fed with a high-fat diet (HFD) for 18 weeks were used to establish atherosclerosis model. Oil-Red-O staining of the plaques in the aorta and the heart was used to determine the severity of atherosclerosis. The autophagy flux was evaluated by western blot and reverse transcription quantitative PCR (RT-qPCR). Then triton WR-1339 (TWR) was injected into muscles of C57BL/6 mice, and the role of autophagy was assessed by autophagy inhibitor LY294002 intervention. The transmission electron microscopy (TEM) and immunofluorescence microscopy analysis (IFM) were used to elucidate the lipid-lowering mechanism of apigenin.Results In HFD-induced mice, apigenin inhibited the dangerous progression of atherosclerosis through decreasing lipid deposition in plaques, lowering serum and liver lipid contents, activating autophagy and promoting reverse cholesterol transport (RCT). In TWR-induced mice, apigenin reduced the serum and liver lipid levels, enhanced the autophagy flux and increased RCT, but the above effects of apigenin were weakened by LY294002. The TEM and IFM images revealed that apigenin promoted the formation of autophagosomes and the co-localization between autophagy proteins with lipid protein.Discussion and conclusions The lipid-lowering effects of apigenin were mediated through promoting RCT and enhancing selective lipophagy, meanwhile it provided a potential therapeutic option for atherosclerosis.